BOOK REVIEW Holly Lawford-Smith GENDER-CRITICAL FEMINISM - Eugen Golubić (European Journal of Analytic Philosophy)
This is a review of the book Holly Lawford-Smith GENDER-CRITICAL FEMINISM, Oxford University Press, 2022.